Navigating curriculum reform: Self-efficacy of Islamic religious education teachers in Indonesia’s Merdeka Curriculum implementation - Muslihudin Muslihudin; Anisatun Muthia; Abd. Rachman Mildan (AL-TARBIYAH: Jurnal Pendidikan (The Educational Journal), 2025)
The Merdeka Curriculum represents a educational policy reform currently being implemented across Indonesia. Its successful execution hinges significantly on teachers’ capacity to adapt, who play a pivotal role in character development. This study aims to examine the level of self-efficacy among Islamic Religious Education (PAI) teachers in implementing the Merdeka Curriculum, identify their strengths and challenges, and propose actionable solutions. A quantitative descriptive survey design was employed, involving 78 PAI teachers enrolled in the Professional Teacher Education Program (PPG) at UIN Siber Syekh Nurjati Cirebon who completed a self-assessment questionnaire measuring multiple dimensions of self-efficacy based on Bandura’s theoretical framework. Results indicate a high level of self-efficacy among PAI teachers in understanding the conceptual foundations of the Merdeka Curriculum (mean > 4.0). However, self-efficacy scores were moderately lower regarding practical application skills (mean > 3.8), with most teachers reporting an overall "Good" level of confidence. The study affirms the relevance of Bandura’s self-efficacy theory in educational reform contexts, highlighting mastery experiences as a key contributor to teacher confidence. It concludes that fostering teacher self-efficacy should be embedded within curriculum reform strategies, emphasizing professional development programs that move beyond knowledge transmission to include authentic and experiential learning opportunities.